2019
DOI: 10.1212/wnl.0000000000007857
|View full text |Cite
|
Sign up to set email alerts
|

nVNS sham significantly affects the trigeminal-autonomic reflex

Abstract: ObjectiveTo determine whether high placebo effects observed in recently published clinical noninvasive vagal nerve stimulation (nVNS) trials can be attributed to an active modulation of the trigeminal-autonomic reflex by the sham device.MethodsTwenty-eight healthy participants were investigated in a randomized, controlled, single-blind, within-participant design. The 4 different conditions of no stimulation, regular nVNS of the left cervical vagal nerve, stimulation of the posterior neck with the same device (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The International Headache Society–recommended primary outcome for the reduction in migraine days from run-in to 3 months was −2.26 days with nVNS and −2.06 days with supraorbital transcutaneous stimulation (6,33). The clinical benefit of nVNS in this study, which may have been understated because of the partially active effects of the sham device (28), complements the good tolerability and safety profile of nVNS.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The International Headache Society–recommended primary outcome for the reduction in migraine days from run-in to 3 months was −2.26 days with nVNS and −2.06 days with supraorbital transcutaneous stimulation (6,33). The clinical benefit of nVNS in this study, which may have been understated because of the partially active effects of the sham device (28), complements the good tolerability and safety profile of nVNS.…”
Section: Discussionmentioning
confidence: 77%
“…This study had three notable limitations: a) the vagal activity of the sham device, b) the use of bilateral stimulations, and c) suboptimal subject adherence to the TID treatment regimen. Subsequent to the PREMIUM trial, another study revealed parasympathetic activity caused by the sham device used in this study, indicating vagal activation and representing a key limitation of the current study (28). The vagal activity of the sham device likely decreased the therapeutic gain seen in this study.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…To increase adherence, the PREMIUM II study includes subjects with a higher overall headache burden than those in the original PREMIUM study, who may be more highly motivated to adhere to the three-times-per-day treatment regimen (43). The sham device used in PREMIUM produced some level of vagal activation (55). A modified inactive sham device has been adopted in the PREMIUM II study to address this issue (43).…”
Section: Migrainementioning
confidence: 99%